An evaluation of the application of good manufacturing practices (GMP) in some poultry products factories in Makkah Al-Mukarramah - KSA - Abumalih, Adel Mohammed; Madkour, Mohamed Hussein; AbdEl-Razik, Mohamed Moustafa (Journal of agricultural, environmental and veterinary sciences, 2022)
Food security is considered one of the priorities of governments in the third millennium, especially with the increase in the possibility of natural disasters and political and economic wars, and achieving this comes with achieving close control over food manufacturing operations. In this study, an evaluation of six poultry products factories in Makkah Al-Mukarramah - Kingdom of Saudi Arabia was conducted to measure how good manufacturing practices are applied in those factories. It was noted from the results of evaluating the factories under study that the six factories differed in the levels of the practical application of the standards under audit. Therefore, a set of corrective measures was developed the non-conformities. A set of corrective measures was developed for the non-conformities discovered in the factories under study. Risk assessment based on good industrial and hygienic practices as follows: SHA77 < AAQ88 < NAS66 < AMK < SUP < SUN. Then it became clear how important it is to follow the risk analysis systems in food factories to reach the desired goal, which is to achieve consumer confidence, aiming to achieve self-sufficiency in accordance with the vision of the Kingdom of Saudi Arabia 2030.